A MAN IN THE COURT: EXPLORING THE THEME OF JUSTICE IN AND THEN THERE WERE NONE - Sistiadinita Sistiadinita (STBA Pontianak, 2021)
Having to interact with crime fiction which presumably is considered as ephemeral literature, cannot be an excuse to dissolve the theme of justice inside the plots. Agatha Christie as the Mistress of Complication and Mystery, has written series of murder and mystery fiction since the beginning of twentieth century. And Then There Were None or entitled Ten Little Niggers, one of her masterpieces depicts Christie’s unique disposition of turning perception from ‘detective as criminal solver’ into ‘murderer as justice protector’. This paper seeks to analyze how justice is portrayed and challenged by looking at the characters created by Christie as well as making a more thorough analysis of the symbols and dialogues. The result of this paper portrays that the idea of justice, just like human beings, can be flawed or misinterpreted even by the so- called a man in the court.